2022
DOI: 10.3947/ic.2022.0122
|View full text |Cite
|
Sign up to set email alerts
|

Changing Features of Liver Injury in COVID-19 Patients: Impact of Infection with the SARS-CoV-2 Delta (B.1.617.2) Variants

Abstract: Background There is growing evidence that abnormal liver function tests (LFTs) are common in patients with coronavirus disease 2019 (COVID-19). However, it is not known whether viral involvement in the liver differs according to the strain. We investigated the impact on liver injury in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Delta (B.1.617.2) variants. Materials and Methods We conducted a single-center, retrospective cohort study, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There are not many studies exploring the effect of the different variants on clinical presentations, and as in our study, the SARS-CoV-2 variant was inferred from the period of infection. For example, a recent study demonstrated that liver injury is more common in patients infected with Delta variants [34], and the studied patients were divided into "pre-Delta period" if they were infected between 1 February and 30 November 2020 or in the Delta period between 1 August and 31 August 2021. Yoon et al [35] compared the pulmonary involvement at the Chest CT scan in 88 patients with the Omicron variant to 88 patients with the Delta variant and demonstrated that in hospitalized patients with similar disease severity, the Omicron SARS-CoV-2 variant showed nontypical peribronchovascular pneumonia and less pulmonary vascular involvement than the Delta variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are not many studies exploring the effect of the different variants on clinical presentations, and as in our study, the SARS-CoV-2 variant was inferred from the period of infection. For example, a recent study demonstrated that liver injury is more common in patients infected with Delta variants [34], and the studied patients were divided into "pre-Delta period" if they were infected between 1 February and 30 November 2020 or in the Delta period between 1 August and 31 August 2021. Yoon et al [35] compared the pulmonary involvement at the Chest CT scan in 88 patients with the Omicron variant to 88 patients with the Delta variant and demonstrated that in hospitalized patients with similar disease severity, the Omicron SARS-CoV-2 variant showed nontypical peribronchovascular pneumonia and less pulmonary vascular involvement than the Delta variant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the follow-up differs between groups, although it was longer in Group A with the worst PFTs, that which could suggest an underestimation of their values and so a bigger difference between groups. Some data are missing, mainly on HGT, as well as the possibility of comparing pulmonary function tests before SARS-CoV-2 infection for an assessment of the real impact of infection on lung function [34]. Moreover, the Chest CT scan was not performed for all subjects, and a qualitative analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study conducted by Phipps et al [ 18 ] on 2273 COVID-19 patients in the United States, 45% had mild, 21% had moderate, and 6.4% had a severe liver injury[ 18 ]. The severity of liver injury was significantly associated with the severity of the COVID-19 disease[ 19 ]. Moderate and severe liver injury was found to be more common in patients who required admission to the Intensive Care Unit[ 18 ].…”
Section: Liver Injury Due To Covid-19mentioning
confidence: 99%
“…Moderate and severe liver injury was found to be more common in patients who required admission to the Intensive Care Unit[ 18 ]. However, even asymptomatic infected patients with COVID-19 have the same viral load, and consequently, liver damage can happen with elevation of liver enzymes, but to a lesser extended than the severe symptomatic patients[ 19 ]. Liver injury is more common in patients with high viral load.…”
Section: Liver Injury Due To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation